Standarisasi dari Daun Kirinyuh (Chromolaena odorata) dan Simplisia Kering dari Tiga Daerah yang Berbeda - Ance, Paulina Erlianda; Wijaya, Sumi; Setiawan, Henry Kurnia (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2018)
Siam wead (Chromolaena odorata) is used traditionally for treatment lesoin, amenorrhea, antidiabetic and antimicrobial. Based on previous research, there is no reference about the standardization Siam Weed leaves dried powder. This study aims to determine macroscopic and microscopic of siam weed leaves fresh plant obtained from, Surabaya, to determine the spesific and non spesific quality profile of dried powder of siam weed leaves dried powder obtained from different areas (Bogor, Malang and Surabaya). The spesific parameter that used were identity, organoleptic, microscopic, determination of soluble extract, phytochemical screening, determination chromatogram profile using Thin Layer Chromatography, determination spectrum profile using spektrophotometer UV-Vis and Infrared, determination of alkaloid, phenol and flavonoid content. Non spesific parameters that used were the determination of total ash value, water soluble ash value, acid insoluble ash value, drying losses and pH. Based on result of the study, it was concluded that siam weed fresh plant leaves have elliptico-oblongus shape, acutus shape for the upper and lower base, green colored for the top and bottom surfaces, adge shape for the wavy , 6.4-11.8 (L), 3.3-5.9 (W), wavely leaf rib, fluffy leaf texture, and the position of facing a single, microscopically have the fragments as same as the dried powder fragments, ethanol soluble concentration ≥ 12%, water soluble concentration ≥ 20%, solvent can be used for chromatogram profile in TLC is chloroform : ethyl acetate (15:1), spectral profile with spectrophotometer UV-Vis have wavelength 533.5 nm, 500 nm, 534.5 nm, 501.5 nm, 284.5 nm, 289 nm and 292 nm, spectral profile with IR spectrophotometers have wavenumber 3266.28 cm-1-3282.21 cm-1, 1416.01 cm-1, 1514.53 cm-1, 1514.93 cm-1, 1245.35 cm-1, 1249.52 cm-1 dan 1251.27 cm-1, flavonoid content ≥ 0.4%, phenol content ≥ 1.0% and alkaloid content ≥ 1.0%, total ash content ≤ 14%, water ash soluble ≤ 5%, acid unsoluble ash ≤ 10%, drying losses ≤ 11% and range pH 5-7.